Penguatan Kompetensi Guru PAUD dalam Pembelajaran Seni Tari untuk Meningkatkan Kreativitas dan Budaya Lokal di Desa Sambirejo, Kecamatan Bringin, Kabupaten Semarang - Renistiara Medilianasari; Ni Kadek Aris Rahmadani; Fathin Farah Fadhilah; Yuli Kurniawati Sugiyo Pranoto; Naila Nasywa; Fitri Febri Handayani; Lahenda Widiasmara; Agapea Fenda Sozo Sandeva; Arini Mayang Fauni (Politeknik Piksi Ganesha Indonesia, 2026)
This community service activity aims to strengthen the competence of early childhood teachers in teaching dance as a strategy to enhance creativity and instill local culture in young children in Sambirejo Village, Bringin District, Semarang Regency. The implementation methods include observing the needs of partners, designing programs, providing hands-on training, assisting and conducting evaluations, and monitoring. The results show an improvement in the knowledge, skills, and attitudes of teachers in designing and implementing dance learning that is contextual to the local culture. The outputs of the activity include copyrights, publications in the mass media and the faculty's official website, article publication and a video highlighting the activity. This program contributes to improving the quality of early childhood education services while supporting SDG 4 (Quality Education) and strengthening regional cultural identity.